2011
DOI: 10.1055/s-0031-1280794
|View full text |Cite
|
Sign up to set email alerts
|

Transition from Ziprasidone IM to Oral Formulation in Agitated Patients with Acute Exacerbation of Schizophrenia: An Open Trial

Abstract: Even with the limitations of any non-comparative study, these results suggest that the IM/oral sequential administration of ziprasidone is an effective and well tolerated therapeutic option in the management of acute exacerbations of schizophrenia in agitated patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…In total, 1428 patients had received IM ziprasidone treatment and 836 patients had received IM haloperidol treatment for agitation. The 19 reports included 12 RCTs (ziprasidone versus haloperidol) [1, 7, 912, 14–16, 19, 22, 25], 5 open-label perspective trials [13, 17, 18, 20, 21], and 2 individual case reports [2, 4]. After multiple discussions among the authors, it became clear that one trial had two studies [18] but one of them was also reported in a later larger study [19]; therefore, one of these two studies was excluded from Table 1, which summarizes the characteristics of the included 19 studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 1428 patients had received IM ziprasidone treatment and 836 patients had received IM haloperidol treatment for agitation. The 19 reports included 12 RCTs (ziprasidone versus haloperidol) [1, 7, 912, 14–16, 19, 22, 25], 5 open-label perspective trials [13, 17, 18, 20, 21], and 2 individual case reports [2, 4]. After multiple discussions among the authors, it became clear that one trial had two studies [18] but one of them was also reported in a later larger study [19]; therefore, one of these two studies was excluded from Table 1, which summarizes the characteristics of the included 19 studies.…”
Section: Discussionmentioning
confidence: 99%
“…First, ziprasidone was associated with modest concentration-related QTc increases [20]. Second, an open-label perspective trial showed similar results including (a) one with only 3 subjects having >60 ms prolonged QTc interval [17] and (b) another [13] indicating that IM ziprasidone did not appear to influence atrial and ventricular electrical conduction in drug-free inpatients with schizophrenia. However, the diagnosis of schizophrenia might influence atrial conduction and even be associated with atrial fibrillation.…”
Section: Discussionmentioning
confidence: 99%
“…52 Furthermore, IM ziprasidone has been shown to be at least as effective, if not more effective than IM haloperidol in some studies, with similar risk for QTc prolongation but less EPS. [53][54][55][56] Olanzapine became available for IM use in 2004 and is supported by data from randomized controlled trials and a meta-analysis concluding it as a safe and effective option with comparable efficacy but less EPS than IM haloperidol. 3,57 It was also comparable in efficacy to haloperidol/ promethazine and haloperidol/benzodiazepine combinations.…”
Section: Parenteral Antipsychoticsmentioning
confidence: 99%
“… 52 Furthermore, IM ziprasidone has been shown to be at least as effective, if not more effective than IM haloperidol in some studies, with similar risk for QTc prolongation but less EPS. 53 - 56 …”
Section: Treatment Optionsmentioning
confidence: 99%